INCREASING THE ACTIVITY OF COMMERCIAL BANKS IN THE STOCK MARKET BY INCREASING INVESTMENT ATTRACTIVENESS (World Economics and Finance Bulletin, 2024)
The article reveals the meaning and significance of the concept of "Increasing the activity of commercial banks in the stock market by increasing their investment attractiveness", increasing the activity of commercial banks in the securities market, the level of profitability and liquidity of commercial banks. in attracting financial resources from the capital market through securities, the level of profitability on preferred shares, the relative profitability of corporate bonds, the share of commercial banks in our country in the securities market was analyzed.
Keywords: Investment attractiveness; stock market; securities